Double-dare to be scared - San Souci, Robert D. (New York : Scholastic, 2004)
What$1 (Bs creepier than being lost in the woods all alone? How about being lost in those woods, and sensing that you$1 (Bre not alone? Robert D. San Souci, popular author of Dare to Be Scared, has spun another thirteen masterful tales to keep nightlights burning across the country. Fans of his first book will be thrilled to find not only the same spirit of scary fun, but even deeper, darker twists and surprises. Newcomers will discover something for every (daring) palate, with stories that range from campfire grabbers to unsettling chillers, and combine elements of folklore and pop culture.s